Pencatatan Pernikahan Dan Akta Nikah Sebagai Legalitas Pernikahan Menurut Kompilasi Hukum Islam - Nunung Rodliyah (Law Faculty of Universitas Bandar Lampung, 2013)
According to Islamic marriage law, each oral marriage agreement must fullfill all marriage requrements. For the sake of marriage administration, each marriage events must be registered and the proof of registration is a marriage sertificate issued by the head of The Office of Religion Affairs (KUA) given to the couple. The sertificate proves the couple as a legal spouse to all other parties. A marriage without serificate may be requested to Local District Religion Court for a legal decision (Isbat nikah).